2011
DOI: 10.1007/s12311-011-0308-8
|View full text |Cite
|
Sign up to set email alerts
|

MRI Shows a Region-Specific Pattern of Atrophy in Spinocerebellar Ataxia Type 2

Abstract: In this study, we used manual delineation of high-resolution magnetic resonance imaging (MRI) to determine the spatial and temporal characteristics of the cerebellar atrophy in spinocerebellar ataxia type 2 (SCA2). Ten subjects with SCA2 were compared to ten controls. The volume of the pons, the total cerebellum, and the individual cerebellar lobules were calculated via manual delineation of structural MRI. SCA2 showed substantial global atrophy of the cerebellum. Furthermore, the degeneration was lobule-speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
44
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 29 publications
6
44
0
Order By: Relevance
“…SCA2 showed significant atrophy of the CM, middle lobe, and superior vermis with relative sparing of the posterior-inferior regions of the cerebellum. The above results were consistent with the observations reported in [24, 25]. For SCA3, significant atrophy was found in the CM region and near significant atrophy was found in the anterior lobes.…”
Section: Methodssupporting
confidence: 93%
“…SCA2 showed significant atrophy of the CM, middle lobe, and superior vermis with relative sparing of the posterior-inferior regions of the cerebellum. The above results were consistent with the observations reported in [24, 25]. For SCA3, significant atrophy was found in the CM region and near significant atrophy was found in the anterior lobes.…”
Section: Methodssupporting
confidence: 93%
“…Magnetic resonance imaging (MRI) data are sparse and often comprise only small sample sizes in this orphan disease. The available structural MRI data have so far confirmed the neuropathological findings showing atrophy of the brainstem and cerebellum,6, 7, 8 but there is also some evidence for cortical brain atrophy and microstructural abnormalities in SCA2 patients 9, 10, 11, 12, 13. For preclinical SCA2 mutation carriers, only two structural MRI studies exist.…”
Section: Introductionmentioning
confidence: 68%
“…25 In contrast, extrapolation of cross-sectional data from symptomatic SCA2 patients in another study suggested atrophy of both cerebellum and pons occurring as early as 7 years before onset of symptoms. 26 This pattern of degeneration seemed to be lobule-specific, affecting certain cerebellar subregions and sparing others. This finding of region specificity was supported by Jacobi and coworkers, 12 who demonstrated selective loss of gray matter in lobules V and VI and, additionally, reduced brainstem volumes in preclinical SCA2 carriers.…”
mentioning
confidence: 97%